2019
DOI: 10.1088/1742-6596/1311/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Solar-powered mini-grids and smart metering systems, the solution to Rwanda energy crisis

Abstract: As the population and economy of Rwanda continue to grow, the energy consumption in Rwanda has shown a continuous rise correspondingly to the population and modern socio-economic life desired in the past few decades. According to the Ministry of Infrastructure, Rwanda household access to electricity increased to 52% by September 2018. Not only does 48% of Rwanda’s population have no electricity, but also the grid is not stable where persistent power failures occur. However, the government has invested in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In SSA, the few energy communities that exist are predominantly set up to bridge energy access gaps with underlying concerns such as poverty reduction and improvement in health. However, these communities are gradually emerging as a pathway towards sustainability and resilience for millions of households in the region [44][45][46].…”
Section: Energy Communities In the Context Of Sub-saharan Africamentioning
confidence: 99%
See 4 more Smart Citations
“…In SSA, the few energy communities that exist are predominantly set up to bridge energy access gaps with underlying concerns such as poverty reduction and improvement in health. However, these communities are gradually emerging as a pathway towards sustainability and resilience for millions of households in the region [44][45][46].…”
Section: Energy Communities In the Context Of Sub-saharan Africamentioning
confidence: 99%
“…In our review, we identified that the aforementioned factors associated with energy communities in Europe are either lacking or insufficient in SSA energy projects. Several authors characterise these insufficiencies as key barriers to establishing sustainable energy communities in the region [14,18,19,[44][45][46][47][48][49][50][51].…”
Section: Energy Communities In the Context Of Sub-saharan Africamentioning
confidence: 99%
See 3 more Smart Citations